WhatsApp as a university tutoring resource - Mamani Calcina, Jorge Gilbert (2022)
Tutoring, as a process of accompaniment of university students, has among its purposes identification of and reflection on the various difficulties that can interfere in the development of student competencies. To the same end, the present research explores the possibility of using WhatsApp as a tutoring resource in universities, with an emphasis on identifying and reflecting on the academic, personal, and family problems of students. This case study uses a quasi-experimental approach with a treatment group and a control group intentionally selected at the Escuela Profesional de Educación Secundaria de la Universidad Nacional del Altiplano de Puno, Peru, during the first semester of the 2020 academic year. Data were collected using semi-structured interview guides and individual tutoring cards. The results show that this technological resource improved the university tutoring service among the students in the experimental group. It proved more flexible and attractive to students, who were motivated to externalize and reflect on their personal, family, and academic difficulties and showed increased openness to receiving help in problem solving them. On the other hand, student participation was less active in the control group. These findings affirm that WhatsApp is a resource that can allow more spontaneous and friendly communication between tutors and students, creating a context conducive to achieving the objectives of university tutoring.